Genome-wide association study of hepatitis C virus- and cryoglobulin-related vasculitis. - Zignego, A; Wojcik, G; Cacoub, P; Visentini, M; Casato, M; Mangia, A; Latanich, R; Charles, E; Gragnani, L; Terrier, B; Piazzola, V; Dustin, L; et al. (Nature Publishing Group, 2014)
The host genetic basis of mixed cryoglobulin vasculitis is not well understood and has not been studied in large cohorts. A genome-wide association study was conducted among 356 hepatitis C virus (HCV) RNA-positive individuals with cryoglobulin-related vasculitis and 447 ethnically matched, HCV RNA-positive controls. All cases had both serum cryoglobulins and a vasculitis syndrome. A total of 899 641 markers from the Illumina HumanOmni1-Quad chip were analyzed using logistic regression adjusted for sex, as well as genetically determined ancestry. Replication of select single-nucleotide polymorphisms (SNPs) was conducted using 91 cases and 180 controls, adjusting for sex and country of origin. The most significant associations were identified on chromosome 6 near the NOTCH4 and MHC class II genes. A genome-wide significant association was detected on chromosome 6 at SNP rs9461776 (odds ratio=2.16, P=1.16E-07) between HLA-DRB1 and DQA1: this association was further replicated in additional independent samples (meta-analysis P=7.1 × 10(-9)). A genome-wide significant association with cryoglobulin-related vasculitis was identified with SNPs near NOTCH4 and MHC Class II genes. The two regions are correlated and it is difficult to disentangle which gene is responsible for the association with mixed cryoglobulinemia vasculitis in this extended major histocompatibility complex region.